2013
DOI: 10.1007/s11626-013-9647-8
|View full text |Cite
|
Sign up to set email alerts
|

Myelination and node of Ranvier formation on sensory neurons in a defined in vitro system

Abstract: One of the most important developmental modifications of the nervous system is Schwann cell myelination of axons. Schwann cells ensheath axons to create myelin segments to provide protection to the axon as well as increase the conduction of action potentials. In vitro neuronal systems provide a unique modality to study a variety of factors influencing myelination as well as diseases associated with myelin sheath degradation. This work details the development of a patterned in vitro myelinating dorsal root gang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The use of differentiated peripheral sensory neurons for studying PNS development and injury depends on the ability of the in vitro cells to faithfully recapitulate the functional properties of in vivo sensory neurons particularly in terms of their electrophysiological properties and potential for myelination 14 , 25 , 26 . We first addressed the electrophysiological modality by whole-cell patch-clamp recordings at 35 DIV (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of differentiated peripheral sensory neurons for studying PNS development and injury depends on the ability of the in vitro cells to faithfully recapitulate the functional properties of in vivo sensory neurons particularly in terms of their electrophysiological properties and potential for myelination 14 , 25 , 26 . We first addressed the electrophysiological modality by whole-cell patch-clamp recordings at 35 DIV (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since we observed this close association between the donor Schwann cells and the in vitro derived peripheral sensory neurons we next investigated whether this interaction triggered and supported the process of myelination. Myelin binding protein (MBP) is a major component of compact myelin sheaths 26 and we therefore assessed for the presence of this integral protein in combination with NEFH to demarcate any myelinating Schwann cells that ensheathed the peripheral sensory neurons (Fig. 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…DETA also promotes long-term cell survival because it is non-digestible by matrix proteases secreted by cells [24, 33]. We have observed that DETA is a permissive substrate for a large number of cell types including neurons and glia and have already observed the myelination of sensory neurons [26] and motoneurons by Schwann cells on this substrate [23]. Hence, DETA lends itself to the long-term co-culture of the cell types required for efficient myelin formation.…”
Section: Discussionmentioning
confidence: 99%
“…There are now also some examples that demonstrate that adaptation to FBS-free cell culture does not have a major impact on the robustness of cell culture systems or on the scientific outcome of the studies (Jukić et al, 2016;Oleaga et al, 2016;Rumsey et al, 2013;Stancescu et al, 2015). However, chemically-defined serum-free media have not yet been developed for every cell line or primary culture at this time (Bjare, 1992;Even et al, 2006;Gstraunthaler, 2003;Brunner et al, 2010).…”
Section: The Serum Marketmentioning
confidence: 99%